Hubungan Jumlah Paritas Ibu Hamil dengan Kejadian Berat Bayi Lahir Rendah di Puskesmas Gading Surabaya - Xela Adilla Pramesthi; Minarni Wartiningsih; Subur Prayitno (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2021)
Introduction: The World Health Organization (WHO) defines low birth weight (LBW) as a baby weighing less than 2500 grams. LBW is still a significant global public health issue because of its adverse effects on pregnant women's health. Nulliparity is also linked to low birth weight (LBW) and other factors that complicate pregnancy. Objective: This study aimed to find out if there was a link between maternal parity during pregnancy and the prevalence of LBW at the Gading Health Center in Surabaya. Method: This study is an analytical observational epidemiological study with a case-control approach. Data were analyzed using a comparative study hypothesis test between two variables in two independent sample groups of 40 mothers who have given birth to LBW babies and 40 mothers who have given birth to non-LBW babies. The MCH handbook contained a questionnaire and a health record form for pregnant women, which were used to collect data. The chi-square statistical test was used to analyze the data for this study. Results and discussion: The findings revealed a relationship between the number of parity (p = 0.005) and the occurrence of LBW, as determined by Odd's Ratio (0.214). The number of parities in primiparas mothers who gave birth to LBW and mothers who gave birth to non-LBW was more significant than the number of parities in multiparas. Conclusion: It is possible to conclude that there is a substantial relationship between the number of parities and the occurrence of LBW. To avoid the event of LBW, pregnant women should pay closer attention to the number of parity or the state of giving birth to live or dead children.